Comparative study of different doses of clonidine as an adjuvant with isobaric levobupivacaine for spinal anaesthesia in patients undergoing caesarean section - Neha Maheshwari; Shefali Gautam; Rajni Kapoor; Ravi Prakash; Shobhna Jafa; Rajni Gupta (Wolters Kluwer Medknow Publications, 2019)
Background: Various techniques of central neuraxial blockade have been tried and successfully used for caesarean section surgeries. Nowadays it is must and essential to know the possible effective dose of clonidine to overcome its known side effect like bradycardia, hypotension and sedation for better outcome of mother as well as foetus in lower segment caesarean section. We have conducted such study to compare different doses of clonidine as an adjuvant to intrathecal isobaric levobupivacaine. The plain levobupivacaine has been shown to truly isobaric with respect to CSF of pregnant women and this property got advantage over hyperbaric bupivacaine in its predictable spread. Materials and Methods: There were about 90 cases of emergency caesarean section of more than 37 weeks gestation with ASA physical status class 2 under spinal anaesthesia were randomly divided into three groups of 30 patients each. In all groups we assessed onset, two segment regression and requirement of analgesic in post-operative period, level of motor block by modified bromage scale [Table 1] and sedation by Campbell sedation score [Table 2]. Maternal and foetal hemodynamic was monitored as well. Group A (n = 30) 10 mg of 0.5% (2 ml) isobaric levobupivacaine + 15 mcg clonidine (0.5 ml). Group B (n = 30) 10 mg of 0.5% (2 ml) isobaric levobupivacaine + 30 mcg clonidine (0.5 ml). Group C (n = 30) 10 mg of 0.5% (2 ml) isobaric levobupivacaine + 45 mcg clonidine (0.5 ml). Normal saline was used to make volume of clonidine upto 0.5 ml. Result: Onset of sensory block was highest in group A with significant difference (P value <0.0001) in all three groups. Two segment regression time (in minutes) was highest in group C with significant difference (P value <0.0001) in all three groups. There was fall in systolic blood pressure (SBP) <80% of baseline was found in 0 (0.00%), 10 (33.33%) and 22 (73.33%) patients in group A, B and C respectively while fall in HR <80% of baseline was found in 0 (0.00%), 1 (3.33%) and 19 (63.33%) patients. Sedation score was 1 in 30 (100%) patients in group A, it was 1 in 10 (33.33%), 2 in 20 (66.67%) in group B while it was 1 in 5 (16.77%), 2 in 10 (33.33%) and 3 in 15 (50%) patients in group C. Conclusion: Spinal anaesthesia performed with isobaric 0.5% levobupivacaine with 30 mcg clonidine (Group B) provides better haemodynamic stability, early onset of sensory and motor blockade, decreased requirement of post-operative analgesia.